The Role of Habituation in Instilling Religious Values in Elementary Students - Kurniawan, Machful Indra; Nisa, Khoirun; Amanillah, Alivia Nur; Khoirul, Aprilia Manunggal Putri Al; Hudiyah, Syfaul; Munawaroh, Hidayatul (Procedia of Social Sciences and Humanities, 2024)
Building religious character among elementary school students is a crucial component in the world of education, which can be the foundation for their daily actions and behaviors. In view of this, SD Muhammadiyah 1 Gempol applies the habituation of religious activities in shaping students' religious character. This study aims to examine more concrete strategies in instilling religious values in elementary school students, one of which is using the habituation method. The method used in this research is descriptive qualitative method. Where data collection is done through interviews, observation, and documentation as well as reviewing previous articles relevant to this research. The subjects in this study were students of SD Muhammadiyah 1 Gempol. The results of this study only describe in-depth interviews and observations that have been conducted on research subjects so as to provide a clear picture of the implementation of religious character education through habituation methods. The results of the research at SD Muhammadiyah showed success in increasing the religious value of students carried out through habituation of morning apple activities by reading short letters, asmaul husna, and Muhammadiyah student promises.